Hypodontia. Does the Prevalence and Distribution Pattern Differ in Orthodontic Patients? - Sisman, Yildiray; Uysal, Tancan; Gelgor, Ibrahim Erhan (European Journal of Dentistry, 2007)
Objective: The aim of this study was to document the prevalence of hypodontia in the permanent dentition among a group of Turkish sample who sought orthodontic treatment and to compare present results with the specific findings of other populations. The occurrence was evaluated in relation to gender, specific missing teeth, the location and pattern of distribution in the maxillary and mandibular arches and right and left sides.Materials And Methods: Orthodontic files of 2413 patients (1557 females-mean age: 17.78±5.41 years old and 856 males-mean age:17.02±5.47 years old) which included orthopantomograms, study models, and anamnestic data were examined for evidence of hypodontia.Results: The prevalence of hypodontia was 7.54% (8.09% for female and 6.54% for male). Hypodontia was found considerably more frequently in the maxilla than in the mandible. Similarity in the distribution of missing teeth between the right and left sides was detected. The most frequently missing teeth were the maxillary lateral incisors, followed by the mandibular and maxillary second premolars. The majority of patients had one or two teeth missing, but seldom three or more.Conclusions: Present data for hypodontia were within the wide range reported in the literature. The findings of patients with hypodontia involving the anterior teeth and others missing more than two teeth in the same quadrant were an indication of a great need for orthodontic treatment. By early detection of missing teeth, alternative treatment modalities can be planned and performed with a multidisciplinary team approach. (Eur J Dent 2007;1:167-173)
Keywords: Hypodontia; Patient; Panoramic radiograph; Turkish; Prevalence